Chicken genome: Current status and future opportunities - Burt, David W. (Genome Research, 2005)
The chicken genome sequence is important for several reasons. First, the chicken shared a common ancestor with mammals ∼310 million years ago (Mya) at a phylogenetic distance not previously covered by other genome sequences. It therefore fills a gap in our knowledge and understanding of the evolution and conservation of genes, regulatory sequences, genomes, and karyotypes. The chicken is also a major source of protein in the world, with billions of birds used in meat and egg production each year. It is the first livestock species to be sequenced and so leads the way for others. The sequence and the 2.8 million genetic polymorphisms defined in a parallel project are expected to benefit agriculture and cast new light on animal domestication. Also, as the first bird to be sequenced, it is a model for the 9600 avian species thought to exist today. Many of the features of the chicken genome and its biology make it an ideal organism for studies in development and evolution, along with applications in agriculture and medicine.
10.1101/gr.4141805